FAKTOR PENYEBAB TERJADINYA TINDAK PIDANA ANAK DAN UPAYA PENYELESAIANNYA - Feno Tri Hidayat (Dinamika, 2021)
Today, the problems of children in Indonesia are quite diverse and the mostfrightening thing is that children are in conflict with the law. Because based on data fromthe Indonesian Child Protection Commission during 2011-2017 there were 9,266 (ninethousand two hundred and sixty-six) cases. Juvenile delinquency is in the spotlight.The research method used in this study is empirical juridical, the types of datainclude primary data and secondary data. The data collection is done by interview orinterview and documentation. The data analysis was carried out in a qualitativedescriptive manner.In conclusion (1) the factors that cause criminal acts committed by children, namelythe influence of education, talent factors and environmental influences. The types ofcrimes committed include drug abuse, sexual harassment and sexual intercourse. (2) Inthe process of carrying out an investigation into criminal acts by children at the SampangPolice, this is done by making reports, summoning, arresting, detaining, searching,confiscation, examination, post-mortem , settlement and submission of case files. Inaccordance with Law Number 11 of 2012 concerning Juvenile Criminal Justice SystemArticles 26 to 40. (3) Barriers or obstacles experienced by police investigators incarrying out the investigation process of criminal acts committed by children at theSampang Police have limited time in processing files from criminal act. In criminal actsthat require a visa, the relatively expensive visa fee is considered too burdensome for thevictim. Children are also less proficient in speaking and difficult to cooperate, whencalling, children are sometimes unable to attend and sometimes parents cannotaccompany them.